Infrastructures protection based on heterogeneous networks. (2016) - Bruzzone, Agostino G.; Massei, Marina; Poggi, Simonluca
This paper presents a modelling approach for mapping cyber defence issues with respect to heterogeneous networks; the research is devoted to develop an agent-driven simulation environment able to analyse this problem considering different layers including CIS capabilities, operational issues, system architecture, management processes and human factors. The paper analyses a specific case study to validate and verify the proposed modelling approach; the scenario is focused on a heterogeneous network applied to an extended maritime environment including autonomous underwater vehicles (AUV), sensors, platforms, vessels, satellites and relevant military assets and threats. The present document uses this case study as example of system of systems to be simulated including cyber warfare issues to evaluate their impact on operations.